Poor Outcome due to the Plasmacytoid Variant of Urothelial Carcinoma - Kyotaro Fukuta; Keito Shiozaki; Saki Kobayashi; Ryoichi Nakanishi; Hirofumi Izaki; Kazuya Kanda; Tohru Inai; Eiji Kudo; Tomoya Fukawa; Kunihisa Yamaguchi; Yasuyo Yamamoto; Masayuki Takahashi; et al. (Case Reports in Oncology, 2022)
A 72-year-old man visited our hospital due to pollakiuria and lower abdominal pain. Urinary cytology was positive, and cystoscopy revealed diffuse edematous nonpapillary tumor. We performed transurethral biopsy, and clinical stage T3 plasmacytoid variant of urothelial carcinoma (PUC) was diagnosed. Although we planned for radical cystectomy, peritoneal dissemination and lung and pelvic lymph node metastases appeared 3 weeks after the initial visit. We also planned for chemotherapy; however, the metastases rapidly progressed, and he died 7 weeks after the biopsy. PUC is rare and shows an aggressive clinical course and poor prognosis.